Learning buffer solution based on virtual lab in senior high school - Gulmah Sugiharti; Aldhi Kurnia (Pascasarjana Universitas Negeri Medan, 2021)
This study aims to determine whether there is a difference between the use of virtual lab and real lab media in guided inquiry learning on learning outcomes in the buffer solution material. Both learning media are taught using the same learning model, namely the guided inquiry learning model. The samples in this study were class XI MIPA 3 as the experimental I which was taught with the guided inquiry learning model using virtual lab media and class XI MIPA 6 as the experimental II which was taught by guided inquiry learning model using real lab. The instrument used in this research was a test of learning outcomes chemistry of the buffer solution material. The data analysis technique for hypothesis testing was the two-party t-test statistic. The results of data processing showed that the experimental I had a pretest mean of 26.04 and a mean of posttest 79.53, while the experimental II had a mean pretest of 47.95 and a mean of posttest of 72.84. Hypothesis testing was carried out using two-party t test from the learning outcomes data and it was obtained tcount = 2.201 while ttable = 1.988 for α = 0.05 so that tcount> ttable. So Ha accept, that is, there are differences in student learning outcomes taught by guided inquiry models using virtual lab and real lab media. Meanwhile, the increase in student learning outcomes in guided inquiry classes using virtual labs was 72%, and those using real labs were 52%.Keywords: Virtual lab, Real lab, Guided inquiry, Buffer solutions